Decomposing the large firm wage premium in Germany - Benjamin Lochner; Stefan Seth; Stefanie Wolter (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2020)
We use an extensive, matched employer-employee dataset to analyze the employersize wage relation and its contribution to wage inequality in Germany. Applying models with additive fixed effects for workers and establishments, we document that the large firm wage premium, which has risen over 25 years, has only recently started to decrease. Our estimates show that the recent decline is due to a decrease in the variation of establishment-specific wage premiums both across establishment size groups and within. This decline together with decreasing worker segregation at small firms account for an overall reversal in the trend of increasing wage dispersion.
Keywords: J00; J21; J31; J40; 330; firm size; wage inequality; wage premiums; fixed-effect wage models; firm andworker heterogeneity